A emergência de professoras travestis e transexuais na escola: heteronormatividade e direitos nas figurações sociais contemporâneas - Marco Antonio Torres (2012)
This thesis states that the emergence of transgender teachers is related to the increasing informality gradient, a process that has started since the beginning of the twentieth century. During this period of time, demands for LGBT (Lesbian, Gays, Bisexuals and Transgender) rights and recognition has emerged and experienced substantial increase in recent decades. This led to changes in emotion regimes of groups and subjects who dispute the legitimacy of those demands. The relations of groups and subjects who are involved in those disputes may be considered as similar to what Norbert Elias defined as figurations of the type established versus outsiders. Transgender teachers as part of the group of outsiders gave rise to the question about how they entered and have remained in the teaching profession. The response may be related to the rise of LGBT demands for rights in those social processes in which outsiders are normalized or recognized, or both. The emergence of transgender teachers is related, among other things, to the direction of the social process in which changes of the emotion regime were identified. The concept of social process is important to understand therise of LGBT demands for rights and recognition, and the persistence of the heteronormativity in school. These studies were conducted by the analyses of discourses contained in two empirical corpora. The first corpus contains two documents that were elaborated by groups who are somehow involved with human rights policies. The second corpus consists of interviews with seven transgender teachers. The analyses referred to above constitute the very foundation for the understanding of how the transgender entered the teaching profession and has stayed there. In this context, the relationship of transgender teachers with the LGBT social movement and the development of political and collective identities suggest the direction of the social process. Due to heteronormativity, outsiders may suffer the effects of monopolies ofaffection and rights in the emotional interdependencies, especially by the normalization of their bodies that were historically marked by the stigma of disease and prostitution. It is possible to identify in the interviews with transgender teachers contradictions between their struggle to fit the gender norms and their fight against the naturalization of the gender bythose norms. The required negotiations between transgender teachers and school and between them and the LGBT social movements are important for their permanence in the teaching profession. The solidarity networks and the development of a collective or political identity may be a watershed in the relationship between education and transgender people.